Temperature and cholera toxin B are factors that influence formation of membrane nanotubes in RT4 and T24 urothelial cancer cell lines - Doron Kabaso (Dove Medical Press, 2011)
Doron Kabaso1*, Maruša Lokar1*, Veronika Kralj-Iglic2, Peter Veranic3, Aleš Iglic11Laboratory of Biophysics, Faculty of Electrical Engineering, 2Laboratory of Clinical Biophysics, Faculty of Medicine, 3Institute of Cell Biology, Faculty of Medicine, University of Ljubljana, Ljubljana, Slovenia; *These two authors equally share the first authorshipAbstract: The growth of membrane nanotubes is crucial for intercellular communication in both normal development and pathological conditions. Therefore, identifying factors that influence their stability and formation are important for both basic research and in development of potential treatments of pathological states. Here we investigate the effect of cholera toxin B (CTB) and temperature on two pathological model systems: urothelial cell line RT4, as a model system of a benign tumor, and urothelial cell line T24, as a model system of a metastatic tumor. In particular, the number of intercellular membrane nanotubes (ICNs; ie, membrane nanotubes that bridge neighboring cells) was counted. In comparison with RT4 cells, we reveal a significantly higher number in the density of ICNs in T24 cells not derived from RT4 without treatments (P = 0.005), after 20 minutes at room temperature (P = 0.0007), and following CTB treatment (P = 0.000025). The binding of CTB to GM1–lipid complexes in membrane exvaginations or tips of membrane nanotubes may reduce the positive spontaneous (intrinsic) curvature of GM1–lipid complexes, which may lead to lipid mediated attractive interactions between CTB–GM1–lipid complexes, their aggregation and consequent formation of enlarged spherical tips of nanotubes. The binding of CTB to GM1 molecules in the outer membrane leaflet of membrane exvaginations and tips of membrane nanotubes may also increase the area difference between the two leaflets and in this way facilitate the growth of membrane nanotubes.Keywords: cancer cells, membrane nanotubes, cholera toxin